Does response time predict withdrawal decisions? Lessons from a bank-run experiment - Hubert János Kiss; Ismael Rodríguez-Lara; Alfonso Rosa-Garcia (Hungarian Academy of Sciences, Institute of Economics, 2018)
We study how response time in a laboratory experiment on bank runs affects withdrawal decisions. In our setup, the bank has no fundamental problems, depositors decide equentially (if to keep the money in the bank or to withdraw) and may observe previous decisions depending on the information structure. We consider two levels of difficulty of decisionmaking conditional on the presence of strategic dominance and strategic uncertainty. We posit that i) decisions in information sets characterized by the lack of strategic dominance are more difficult than in those with strategic dominance; ii) in the latter group, decisions are more difficult when there is strategic uncertainty. We investigate how response time associates with the difficulty and optimality of withdrawal decision. We hypothesize that a) the more difficult the decision, the longer the response time; b) the predictive power of response time depends on difficulty. We find that response time is longer in information sets with strategic uncertainty compared to those without (as expected), but we do not find such relationship when considering strategic dominance (contrary to our hypothesis). Response time correlates negatively with optimal decisions in information sets with a dominant strategy (contrary to our expectation) and also when decisions are obvious in the absence of strategic uncertainty (in line with our hypothesis). When there is strategic uncertainty, we find suggestive evidence that response time predicts optimal decisions. Thus, freezing deposits for some time may be beneficial and help to avoid massive withdrawals as it engthens response times.
Keywords: C72; C91; D80; G21; 330; bank run; cognitive abilities; coordination games; dominant strategy; experiment; response time; sequential rationality; strategic uncertainty